2010
DOI: 10.1002/nbm.1573
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the in vivo assessment of pyruvate dehydrogenase activity using hyperpolarised 13C MRS

Abstract: Aim Many diseases of the heart are characterised by changes in substrate utilisation, which is in part regulated by the activity of the enzyme pyruvate dehydrogenase (PDH). Consequently, there is much interest in the in vivo evaluation of PDH activity in a range of physiological and pathological states to obtain information regarding the metabolic mechanisms of cardiac diseases. Hyperpolarized [1-13C]pyruvate, detected using MRS, is a novel technique for evaluating PDH flux non-invasively. PDH flux has been as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
142
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(151 citation statements)
references
References 39 publications
8
142
1
Order By: Relevance
“…With the recent enhancements in the MR sensitivity of the 13 C nucleus achieved using dynamic nuclear polarisation (DNP) (1), it is now possible to complement structural data using MRI with global metabolic information in the myocardium (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Work with several in vivo animal models has combined DNP with different imaging techniques (18)(19)(20)(21)(22), including chemical shift imaging (CSI) (23), to obtain metabolic maps of the heart using hyperpolarised [1-13 C]pyruvate (2,20,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the recent enhancements in the MR sensitivity of the 13 C nucleus achieved using dynamic nuclear polarisation (DNP) (1), it is now possible to complement structural data using MRI with global metabolic information in the myocardium (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Work with several in vivo animal models has combined DNP with different imaging techniques (18)(19)(20)(21)(22), including chemical shift imaging (CSI) (23), to obtain metabolic maps of the heart using hyperpolarised [1-13 C]pyruvate (2,20,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the work described here was to develop a combined DNP and CSI protocol for application in the isolated perfused rat heart to generate metabolic images of hyperpolarised [1][2][3][4][5][6][7][8][9][10][11][12][13] (5,13). It should be possible to generate maps of these metabolites in the isolated perfused rat heart and to use the metabolic images of [1- 13 C]pyruvate as a marker of tissue perfusion, [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate as a marker of anaerobic metabolism and [ 13 C]bicarbonate as a marker of aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, these studies have been focused primarily on PDH activity, which, given its pivotal position in the glucosefatty acid cycle, has allowed further insight into cardiac substrate selection 67 and have again shown that in vivo real-time PDH activity is decreased in diabetic 68 and high-fat diet animal models. 69 Furthermore, in addition to the effects of increased fatty acid uptake and utilization on the production of the electrochemical gradient that powers ATP production, there is now evidence that there are intrinsic defects in the metabolic machinery of the electron transport chain (complexes I, III and IV) in human and animal models of obesity, with electron transport chain function and efficiency being reduced. [70][71][72][73]35 As a result of the evidence that substrate selection alters myocardial efficiency, several novel therapies have been evaluated in the setting of ischemia, a situation where reducing myocardial oxygen consumption without decreasing cardiac work would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…These diabetic rats also had increased blood glucose levels, decreased insulin, and increased hepatic triglycerides. Decreased production of hepatic [1][2][3][4][5][6][7][8][9][10][11][12][13] C]alanine was observed in the diabetic group, but this change was not present in the hearts of the same diabetic animals.…”
mentioning
confidence: 98%